Respuesta :

The general equation of an ellipse is

[tex] \dfrac{(x-x_0)^2}{a^2}+\dfrac{(y-y_0)^2}{b^2} = 1 [/tex]

where:

  • [tex] x_0 [/tex] is the x coordinate of the center
  • [tex] y_0 [/tex] is the y coordinate of the center
  • [tex] a [/tex] is half the length of the major axis
  • [tex] b [/tex] is half the length of the minor axis

So, in your case, we have [tex] (x_0,y_0)=(2,3) [/tex], and the equation will look like this:

[tex] \dfrac{(x-2)^2}{a^2}+\dfrac{(y-3)^2}{b^2} = 1 [/tex]

Moreover, we know that the major axis is horizontal (i.e. it involves the x coordinate). Its length is 8, which implies [tex] a=4 [/tex]

Similarly, the minor axis has length 4, which implies [tex] b=2 [/tex]

So, the complete equation is

[tex] \dfrac{(x-2)^2}{16}+\dfrac{(y-3)^2}{4} = 1 [/tex]

ACCESS MORE